Regulation of Stem Cell Differentiation by Inorganic Nanomaterials: Recent Advances in Regenerative Medicine - He, Fumei; Cao, Jinxiu; Qi, Junyang; Liu, Zeqi; Liu, Gan; Deng, Wenbin (Frontiers in Bioengineering and Biotechnology, 2021)
Transplanting stem cells with the abilities of self-renewal and differentiation is one of the most effective ways to treat many diseases. In order to optimize the therapeutic effect of stem cell transplantation, it is necessary to intervene in stem cell differentiation. Inorganic nanomaterials (NMs), due to their unique physical and chemical properties, can affect the adhesion, migration, proliferation and differentiation of stem cells. In addition, inorganic NMs have huge specific surface area and modifiability that can be used as vectors to transport plasmids, proteins or small molecules to further interfere with the fate of stem cells. In this mini review, we summarized the recent advances of common inorganic NMs in regulating stem cells differentiation, and the effects of the stiffness, size and shape of inorganic NMs on stem cell behavior were discussed. In addition, we further analyzed the existing obstacles and corresponding perspectives of the application of inorganic NMs in the field of stem cells.